MITOLOGI SENI REOG PONOROGO VS KAMPANYE PERLINDUNGAN SATWA ANIMAL WALFARE MELALUI PRAKTIK REKAYASA SOSIAL - Jusuf Harsono; Slamet Santoso; Yusuf Adam Hilman (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2020)
The Mythology of Ponorogo’s Reog vs The Animal Walfare Campaign through Social Engineering Practice. Community beliefs in using tiger’s skin considered as an important thing for Ponorogo’s Reyog artist. However, this intensely opposed to Animal Welfare Conception. Therefore, it needs against the reality of deconstruction. This study seeks to change the Ponorogo’s Reyog artist mindset. It can be change slowly by Social Engineering. This study using a qualitative methodology with the approach of phenomenology. Informants in this review are craftsman of Reyog and the artist. The study obtained the procedure of making craft, Dhadhak Merak (Barongan). By using substitute material, the cost are difference. It is cheaper. The dissemination of information through media-related making craft Dhadhak Merak (Barongan) Subtitusi made. Through the medium of as a newspaper, that readily in were missing by the community is a form of campaign As Social-Engineering practices of measurable.